Black beauty - Church, Lisa R., 1960-; Corvino, Lucy.; Sewell, Anna, 1820-1878. (New York : Sterling, 2005)
An abridged version of Black Beauty's experiences with both good and bad masters in nineteenth-century England.
Includes audiobooks.
Keywords: Audiobooks, English; Horses -- Fiction